“MELON-EATING MASSES”: CONSUMER-CITIZENS AND PUBLIC INTERNET DISCOURSE IN CHINA - Wong, Jamie; Long, Vesper; Qu, Yilia; Jones, Graham (AoIR Selected Papers of Internet Research, 2023)
This paper examines how the state, neoliberal capitalism, and digital mass media converge to shape particular kind of Chinese “consumer-citizen” (Mazzarella 2013) public: the “melon-eating masses.” By examining how Chinese internet users participate in a genre of public gossip vernacularly known as “melon eating” when the state looms as the final arbiter of judgement, this study illuminates how the politics of “knowing what not to know” (Hillenbrand 2020) unfold in day-to-day (digital) lives in China. Through attending to the “social poetics” (Herzfeld 1988) of netizens’ performance of “rationality” and their understanding and stereotyping of each other, we show how domestic social imaginaries of the Chinese nation and the “rational” Chinese consumer-citizen are co-produced (Jasanoff 2004; Erickson et al 2013), and how they serve to deflect criticism from the Chinese state. Building on anthropological scholarship on gossip as a form of social control (Merry 1984), we explore how public gossiping becomes incorporated into the state’s panoptic apparatus. As Chinese internet users form “partial theories” about “relationships and events” (Van Vleet 2003) through public gossip, “melon-eating” can paradoxically normalize the unknowability of truth under an already-opaque governmental regime.